Penggunaan Media Seven in One dalam Pembelajaran Matematika Madrasah Ibtidaiyah - Tria Marvida; Zainal Abidin; Nida Jarmita (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The problem in this study is the use of media in the process of learning mathematics with flat building materials. Of the many media that can be used, Seven In One is one of the most suitable media used to teach flat material. The purpose of this study was to find out the difference in learning outcomes between students taught and Seven In One media and learning without Seven In One media. The method used in this study is the experiment method using data collection techniques. That is, ask Pre-Test and Post-Test questions. The research was conducted at MIN 46 Aceh Besar school with a research sample of 38 grade IV students. The approach used is a quantitative approach that uses data analysis techniques to test normality, homogeneity, and hypothesis testing. Based on the results of the data analysis can be concluded that there are differences in student learning outcomes that are studied with Media Seven In One.